Students' English Speaking Anxiety: Levels and Causes - Yusuf, Nabilla Yoes Catur; Yulianto, Slamet Wahyudi; Maulida, Ida (Siliwangi University, 2023)
Learning English especially speaking is very difficult for students. There are many components that students must master when learning speaking makes it difficult for students to learn it. Students find many problems when speaking such as speaking anxiety. Speaking anxiety is a feeling of excessive anxiety when students speak English. Hence, this study aims to find the levels and factors that cause speaking anxiety among the students. This study was conducted at one of English Education Study Program of a university located in Subang, West Java, Indonesia, which consisted of 20 students from first, second, third, and fourth year. This descriptive study used questionnaire and interview to obtain the data about students’ speaking anxiety. In this case, the questionnaire was used to examine the levels of students’ speaking anxiety, while the interview was employed to investigate the factors that causing students’ speaking anxiety. Results from the questionnaire showed that 4 students (20%) scored low, 9 students (45%) scored moderate, and 7 students (35%) scored high. No semester differences were identified in the level of speaking anxiety. Female students exhibited greater nervousness when speaking English compared to male classmates. The interview results revealed three elements contributing to students' speaking anxiety: communication apprehension, test anxiety, and fear of unfavourable evaluation. Communication apprehension is the primary element influencing pupils' speaking anxiety. This study indicates that students need to be aware of their anxiety levels and causes in order to address them. Additionally, they need to possess self-confidence in learning English, particularly in speaking. Keywords: speaking, anxiety, speaking anxiety, students’ speaking anxiety